2016
DOI: 10.7863/ultra.15.06060
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an Advanced Ultrasound Elective

Abstract: The longitudinal undergraduate medical education ultrasound elective produced physicians who were more likely to seek additional training in residency, evaluate themselves as more proficient, and use ultrasound in their clinical practice. Early training in bedside ultrasound during undergraduate medical education yields physicians who are better prepared for integration of ultrasound into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Curriculum surveys [20][21][22][23][24] Five papers featured surveys of curriculum administrators regarding incorporation of ultrasound into medical schools in the USA. Bahner [20] provides a useful cross-section of ultrasound teaching in the USA, where 62.2% of schools that responded reported that ultrasound was a part of their medical school curriculum.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
See 1 more Smart Citation
“…Curriculum surveys [20][21][22][23][24] Five papers featured surveys of curriculum administrators regarding incorporation of ultrasound into medical schools in the USA. Bahner [20] provides a useful cross-section of ultrasound teaching in the USA, where 62.2% of schools that responded reported that ultrasound was a part of their medical school curriculum.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…The benefits of active student engagement and leadership have also been demonstrated in student-led ultrasound interest groups [102], where students interested in ultrasound have the opportunity to organise educational events and demonstrate autonomy in their learning. Medical students respond positively to US and, after receiving undergraduate ultrasound instruction, are more likely to use US in their postgraduate practice [24].…”
Section: Harness Student Enthusiasmmentioning
confidence: 99%
“…Ultrasound curricula have been formalized in 28% of medical schools, with longitudinal implementation described through workshops within the preclinical years and electives or clinical tracks in the senior years . At Yale School of Medicine (YSM), we have been piloting POCUS teaching to a proportion of medical students with emphasis on using a small‐group format during regular biweekly bedside tutorials.…”
mentioning
confidence: 99%
“…26 Ultrasound curricula have been formalized in 28% of medical schools, 24 with longitudinal implementation described through workshops within the preclinical years and electives or clinical tracks in the senior years. 22,[28][29][30][31] At Yale School of Medicine (YSM), we have been piloting POCUS teaching to a proportion of medical students with emphasis on using a small-group format during regular biweekly bedside tutorials. Recent studies illustrate the accuracy and feasibility of application-specific POCUS examinations performed by medical students, 4,9,11 but there is a paucity of data on the effect of POCUS integration on established preclinical assessments.…”
mentioning
confidence: 99%
“…Furthermore, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic greatly impacted medical education, especially ultrasound education, which has traditionally depended on hands-on practice and instruction. Evidence suggests that medical school training may positively impact graduates' ultrasound use in subsequent practice [ 11 ]. At the UME level, ultrasound in anatomy education traditionally relied on structured teaching by faculty proctors trained in ultrasound.…”
Section: Introductionmentioning
confidence: 99%